An investigation into the prevalence and use of code switching practices in grade 8 mathematics classrooms in the Ohangwena region of Namibia: a case study - Shilamba, Julia Ndinoshisho (Rhodes University, Faculty of Education, Department of Education, 2013)
This research report focuses on an investigation of the prevalence and nature of code switching practices in grade 8 mathematics classrooms in the Ohangwena region of Namibia. The existence of code switching in these classrooms was established by administering a survey to all grade 8 teachers in the region, while the nature of these practices was explored by interviewing and observing selected teachers using a case study research methodology. The data from the survey was analysed quantitatively using descriptive statistics, while the qualitative data from the case study which comprised of audio and video transcripts was analysed within the framework of Probyn's (2006) code switching categories. These categories looked at code switching in terms of: explaining concepts; clarifying statements or questions; emphasising points; making connections with learners' own contexts and experiences; maintaining the learners' attention with question tags; classroom management and maintaining discipline; and affective purposes. The study found that code switching is widespread in most of the grade 8 mathematics classrooms in the Ohangwena region. It also revealed that the teachers' code switching practices aligned well with most of Probyn's framework. The criterion of maintaining learner's attention with question tags was however not found in this study. The results of the study showed that teachers code switch because the majority of the learners' language proficiency is not good. Code switching is mostly used as a strategy to support and promote learners understanding in mathematics. The study recommends that it is high time that code switching is acknowledged as a legitimate practice and recognised as an important and meaningful teaching strategy to assist learners who are learning mathematics in their second language. Code switching needs to be de-stigmatised and teachers should be supported in using this practice effectively and efficiently.
Keywords: Mathematics -- Study and teaching (Secondary) -- Namibia -- Ohangwena; Mathematics teachers -- Education (Secondary) -- Namibia -- Ohangwena; Code switching (Linguistics) -- Research -- Namibia -- Ohangwena; Education, Secondary -- Namibia -- Ohangwena